Predictors of Hearing Loss in Premature Newborns - O.P. Melnichuk (Zaslavsky O.Yu., 2013)
One of the most important problems of the perinatal period in premature infants is hearing disorder. Hearing test was performed in 1537 preterm infants with a gestational age of 22 to 36 weeks, they underwent medical treatment at the Kharkiv city perinatal center from 2009 to 2012. Newborn hearing screening was performed using the device OtoRead (Denmark). In the course of the research results of screening «test passed» was recorded in 893 preterm infants, representing 67.9 % of all children examined in primary screening. Result «test failed» was recorded in 388 children (30.3 % of the children in the primary screening). Children with screening result «test failed» binaural were 237 (18.5 % of patients), with screening result «test failed» in one ear - 151 (11.8 % of the surveyed during the primary screening). In the study of hearing in preterm infants with a gestational age less than 28 weeks we found the following: «test passed» - 6 (13.6 %) children, «test failed»: 31 (70.4 %) child - binaural and 7 (16 %) children - in one ear. The rate of hearing impairments in newborns with perinatal pathology is much higher than population-based indicators.